Establishing a valid construct of fear of childbirth: findings from in-depth interviews with women and midwives - P. Slade; K. Balling; K. Sheen; G. Houghton (BMC, 2019)
Abstract Background Fear of childbirth (FOC) can have a negative impact on a woman's psychological wellbeing during pregnancy and her experience of birth. It has also been associated with adverse obstetric outcomes and postpartum mental health difficulties. However the FOC construct is itself poorly defined. This study aimed to systematically identify the key elements of FOC as reported by women themselves. Methods Semi-structured interviews with pregnant women (n = 10) who reported to be fearful of childbirth and telephone interviews with consultant midwives (n = 13) who regularly work with women who are fearful of childbirth were conducted. Interviews were analysed using thematic analysis for each group independently to provide two sources of information. Findings were reviewed in conjunction with a third source, a recently published meta-synthesis of existing literature of women's own accounts of FOC. The key elements of FOC were determined via presence in two out of the three sources at least one of which was from women themselves, i.e. the reports of the women interviewed or the meta-synthesis. Results Seven themes were identified by the women and the consultant midwives: Fear of not knowing and not being able to plan for the unpredictable, Fear of harm or stress to the baby, Fear of inability to cope with the pain, Fear of harm to self in labour and postnatally, Fear of being 'done to', Fear of not having a voice in decision making and Fear of being abandoned and alone. One further theme was generated by the women and supported by the reports included the meta-synthesis: Fear about my body's ability to give birth. Two further themes were generated by the consultant midwives and were present also in the meta-synthesis: Fear of internal loss of control and Terrified of birth and not knowing why. Conclusions Ten key elements in women's FOC were identified. These can now be used to inform development of measurement tools with verified content validity to identify women experiencing FOC, to support timely access to support during pregnancy.